(untitled) (Archives of Clinical Psychiatry, 2013)
BACKGROUND: The use of intervention strategies aimed at dementia caregivers objectives the information and the creation of coping strategies to deal with the difficulties caused by dementia. OBJECTIVES: To assess the correlation between the participation in a psychoeducational group and the decrease of burden, and depressive and anxious symptoms of caregivers of people with dementia. METHODS: Caregivers (n = 18) assessed in a longitudinal study at baseline and after six months of participation in a psychoeducational group. There were used the Clinical Dementia Rating (CDR), Pfeffer Functional Activities Questionnaire (PFAQ), Cornell Scale for Depression in Dementia (CSDD), Quality of Life Scale in Alzheimer' Disease (QoL-AD), Neuropsychiatric Inventory (NPI), Zarit Burden Interview (ZBI), Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI). RESULTS: In the baseline, there was correlation between the burden and the caregivers' depressive symptoms (p = 0.048). The analysis of the differences between the baseline and the second moment has shown a decrease in caregivers' depressive symptoms in moment 2 (p = 0.011). There were no significant differences in the other variables. DISCUSSION: Psychoeducational groups can be considered efficient interventions on the decrease of the depression of caregivers of people with dementia.